Novel Insight Into the Molecular and Metabolic Mechanisms Orchestrating IL-17 Production in γδ T Cells - Chen, Xu; Morrissey, Samantha; Chen, Fuxiang; Yan, Jun (Frontiers in Immunology, 2019)
Increasing evidence has demonstrated that IL-17-producing γδ T cells (γδ T17) play a tumor-promoting role in a series of cancers via various mechanisms in mice and human cancers, though the relationship between γδ T17 and human tumors has yet to be extensively characterized and established. Molecular signals such as intrinsic cascade, environmental cues and cellular metabolic pathways including nutrient uptake and utilization in γδ T17 cells are significantly important for their activation, differentiation and function. Understanding the molecular mechanisms and metabolic pathways of γδ T17 cells in both the physiological setting and tumor environment would contribute to the development of therapeutic approaches or drugs targeting γδ T17 for immunotherapy in cancers.